METODE THRESHOLD SOFTWARE IMAGE-J DALAM PENENTUAN UKURAN PORI MASKER DAN KAITANNYA TERHADAP INTENSITAS SERAP CAHAYA - Jumardin, Jumardin (SAINFIS: Jurnal Sains Fisika, 2024)
This research was carried out to determine the comparison of the pore sizes of medical masks and non-medical masks using image-J software with the threshold method and the relationship between light intensity and the pore size of the masks.. The samples used in the research were three types of medical masks and two types of medical masks. This research uses the threshold method found in image-J software to distinguish the background of the object under study. The image capture process uses a digital microscope camera with a magnification of 50-1600 times, then the image is processed in Image-J software to determine the pore size of medical masks and medical masks. Based on research data, the smallest ratio of pore sizes for medical masks and medical masks is 0.093 mm : 0.161 mm. Medical masks have smaller pore sizes than medical masks. The relationship between light intensity and medical mask pore size is directly proportional. Medical masks have the smallest pore size and low light intensity values (0.0089 Lux/cm). Non medical masks had the highest intensity value (0.0133 Lux/cm).